2020
DOI: 10.21608/aimj.2020.27457.1190
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Subcostal Transversus Abdominis Plane Block For Postoperative Analgesia After Laparoscopic Cholecystectomy ( comparative Study Between Bubivacaine Versus Bubivacaine-Ketamine)

Abstract: Background: Laparoscopic cholecystectomy is the surgery to remove the gall bladder and is the common treatment of symptomatic gall stone and other GB conditions. Laparoscpic cholecystectomy can be carried out under general anaesthesiathat is often related to chronic postoperative pain. Aim of work: Study Compares between adding ketamine to bupivacaine and bupivacaine alone for postoperative pain in patients undergoing ultrasound guided subcostal transversus abdominis plane block (TAPB) after laparoscopic chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…On the contrary, Medhat et al [15] reported no difference between the study groups regarding the time of the first analgesic request and opioid consumption in the subcostal transversus abdominis plane block in laparoscopic cholecystectomy. This may be attributed to the use of a small dose of ketamine [0.5 mg/kg] while we used [2 mg/kg] in our study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the contrary, Medhat et al [15] reported no difference between the study groups regarding the time of the first analgesic request and opioid consumption in the subcostal transversus abdominis plane block in laparoscopic cholecystectomy. This may be attributed to the use of a small dose of ketamine [0.5 mg/kg] while we used [2 mg/kg] in our study.…”
Section: Discussionmentioning
confidence: 94%
“…On the contrary, Medhat et al [15] reported that insignificant difference was found between bupivacaine versus bupivacaine ketamine groups regarding visual analogue scale after laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 95%